PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD ZENDING HKBP - Basri, Basri; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low learning outcomes of PKN students of class V SD Zending HKBP Private Hutan Ayu, with an average value of 62.71. This study is a classroom action research conducted two cycles, carried out in the even semester of 2016/2017. The subjects of this study were 24 students. This study aims to improve the learning outcomes of Vocational School students of Private Primary School V Zending HKBP Hutan Ayu by applying the Inside Outside Circle learning model. This research instrument consists of learning tools and data collection instruments. Data analysis technique used is staistik analysis by analyzing data obtained from activity observation sheet of teacher and student as well as student learning result. Data analysis techniques on teacher and student activities are based on observations using observation sheets during the implementation of the action. While the data analysis of student learning outcomes to see the improvement of student learning outcomes and completeness of learning outcomes. Based on the data analysis from the observation sheet of teacher and student activity, there were improvement of learning quality such as: teacher activity in cycle I reached 58.33%, cycle II reached 91.67% while student activity cycle I reached 50%, cycle II reached 83.33 %. Analysis of student learning result data showed improvement that is from 62,71 at initial data increase in cycle I become 70,42. Furthermore, on the second cycles, the learning outcomes increased to 74.79. From the data is known there is an increase of 19.27%. Besides the increased learning outcomes, the implementation of IOC also increased the number of students who completed. In the initial data of students who are not complete there are 15 people from 24 students. In the second cycle students have completed all (100%) of these findings indicate that the implementation of IOC learning model can improve learning outcomes PKN V grade students Private Private Zending Hutan Ayu.Keywords: IOC Model, Learning Outcomes Civics